2021
DOI: 10.1139/cjb-2020-0179
|View full text |Cite
|
Sign up to set email alerts
|

DKW basal salts improve micropropagation and callogenesis compared with MS basal salts in multiple commercial cultivars ofCannabis sativa

Abstract: Existing Cannabis sativa micropropagation protocols use a limited number of cultivars and are often not reproducible. Currently, MS + 0.5 μM TDZ has been reported as the optimal medium for nodal micropropagation, yet our preliminary studies with this medium have resulted in abnormal morphology and high mortality rates in multiple cultivars. Following an initial screen of basal salt mixtures (MS, B5, BABI, and DKW), we determined that DKW produced the healthiest plants. In a second experiment, the multiplicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 33 publications
8
42
1
Order By: Relevance
“…As such, it can be concluded that either this method is not suitable for inducing de novo regeneration across different genotypes, or that one or more of the details that could not be accurately replicated (Table 1) are critical for success. Regardless, these data highlight previous observations that Cannabis is a relatively recalcitrant species [6,9,13,22,32] and care must be taken to include multiple genotypes and detailed descriptions of experimental designs to ensure reproducible methods.…”
Section: Plos Onesupporting
confidence: 56%
See 4 more Smart Citations
“…As such, it can be concluded that either this method is not suitable for inducing de novo regeneration across different genotypes, or that one or more of the details that could not be accurately replicated (Table 1) are critical for success. Regardless, these data highlight previous observations that Cannabis is a relatively recalcitrant species [6,9,13,22,32] and care must be taken to include multiple genotypes and detailed descriptions of experimental designs to ensure reproducible methods.…”
Section: Plos Onesupporting
confidence: 56%
“…All leaf material was sourced from in vitro shoots maintained within a long-term in vitro germplasm at the University of Guelph. All explants used in this experiment were from Stage 2 in vitro grown shoots maintained as previously described [6,13]. The plants had been in a state of vegetative growth for at least 6 months and were routinely subcultured ever 4-6 weeks.…”
Section: Regeneration From Leaf-derived Explantsmentioning
confidence: 99%
See 3 more Smart Citations